Report and Lament – Załmen Gradowski’s Notes from Auschwitz - Adamczyk, Kazimierz (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
Notes of Załmen Gradowski, one of the leaders of the Sonderkommando revolt in Auschwitz-Birkenau, is one of the most important documents of the Holocaust produced by his victims during the crime and at its epicenter. Their fragments were published in Poland and Israel. Gradowski was a religious Jew from Grodno, he prayed daily in the camp and wrote down transport information. His family: mother, wife and children, immediately after arriving in Auschwitz, were murdered in gas chambers. The author analyzes the literary value of this extraordinary document, which consists of narrative diary entries and imaginative lyrical inscriptions, rooted in the Jewish tradition of conversation with God. So we read the records of the nature of the report and lament. This unique record – given its place of origin and literary values – a testimony of the crimes committed against and suffering of the victims of the Holocaust once again asks us about the inexpressibility of the Holocaust.